Guidelines for rapid assessment of minor irrigation systems in Sri Lanka - Groenfeldt, D. (International Irrigation Management Institute, 1989)
This paper presents a set of guidelines for rapid evaluation of an irrigation system, developed by IIMI staff in cooperation with staff from the Regional Development Division and Badulla District office of the Integrated Development Projects. A one-day workshop on rapid assessment methodologies suitable for minor (small-scale) irrigation systems in Sri Lanka was held at IIMI Headquarters in August 1988. Representatives who participated in ongoing projects to improve minor irrigation systems were from the three Sri Lankan agencies, the Irrigation Department, the Department of Agrarian Services, and the Regional Development Division of the Ministry of Plan Implementation, which oversees the district-level Integrated Rural Development Projects.